(untitled) (Research, Society and Development, 2022)
Objective: To characterize and analyze the management and structure of Pharmaceutical Assistance in the twelve municipalities of a Health Region of Rio Grande do Sul and to identify the challenges and advances in the organization of services based on the perception of actors involved in the work processes. Method: This is a cross-sectional study in which the source of information were professionals and managers of the Brazilian public health system at the municipal level. Data collection occurred in 2021, through individual remote interviews, with the application of semi-structured questionnaires and the data were analyzed in a qualitative-quantitative way. Results: The characterization of Pharmaceutical Assistance is heterogeneous, with particularities among the municipalities. Fragilities were identified regarding budget deficits, infrastructure, and operational capacity, as well as difficulties in formalizing the Pharmacy and Therapeutics Commission and Municipal Medicines List. In addition, there was insufficient integration of Pharmaceutical Assistance with the different points of health care and predominantly drug-focused vision. Such barriers compromise the integrality of care. As potentialities in the municipalities of the region, normative aspects and the participation of the pharmacist in the planning and management instruments, in addition to the sensitization of some managers regarding the performance focused on patient care, stood out. Conclusion: Overcoming the fragmentation of actions and the restrictive view of medication as a commodity requires support from managers and consolidation of participatory planning.